VLBI observations of bright AGN jets with the KVN and VERA Array (KaVA): Evaluation of imaging capability - Niinuma, Kotaro; Lee, Sang-Sung; Kino, Motoki; Sohn, Bong Won; Akiyama, Kazunori; Zhao, Guang-Yao; Sawada-Satoh, Satoko; Trippe, Sascha; Hada, Kazuhiro; Jung, Taehyun; Hagiwara, Yoshiaki; Dodson, Richard; et al. (Publications of the Astronomical Society of Japan, 2014)
The Korean very-long-baseline interferometry (VLBI) network (KVN) and VLBI Exploration of Radio Astrometry (VERA) Array (KaVA) is the first international VLBI array dedicated to high-frequency (23–43 GHz bands) observations in East Asia. Here, we report the first imaging observations of three bright active galactic nuclei (AGNs) known for their complex morphologies: 4C 39.25, 3C 273, and M 87. This is one of the initial results of KaVA's early operation. Our KaVA images reveal extended outflows with complex substructures such as knots and limb brightening, in agreement with previous Very Long Baseline Array (VLBA) observations. Angular resolutions are better than 1.4 and 0.8 mas at 23 and 43 GHz, respectively. KaVA achieves a high dynamic range of ∼ 1000, more than three times the value achieved by VERA. We conclude that KaVA is a powerful array with a great potential for the study of AGN outflows, at least comparable to the best existing radio interferometric arrays.